2023
DOI: 10.55782/ane-2022-042
|View full text |Cite
|
Sign up to set email alerts
|

Mitochonic acid 5 promotes the migration of mouse microglial BV‑2 cells in the presence of LPS‑induced inflammation via Mfn2‑associated mitophagy

Abstract: Effective strategies are needed to prevent the development of neuroinflammation, which is associated with nervous system disease, in patients. A previous study indicated that mitochonic acid 5 (MA‑5) may promote the survival of microglial cells via mitofusin 2 (Mfn2)‑associated mitophagy in response to lipopolysaccharide (LPS)‑induced inflammation. The current study investigated the role and underlying mechanisms of MA‑5 in the migration of BV‑2 cells following LPS‑mediated inflammation. The results of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent evidence highlights the mitochondrial fusion protein MFN2 in regulating host immune responses, especially in the virus-induced RLR signaling pathway (Eisenächer and Krug 2012 ; Tan et al 2022 ; Xu et al 2020 ). In this study, we observed an increase in the expression level of Lc MFN2 following poly(I:C) stimulation, suggesting its potential involvement in the regulation of antiviral immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence highlights the mitochondrial fusion protein MFN2 in regulating host immune responses, especially in the virus-induced RLR signaling pathway (Eisenächer and Krug 2012 ; Tan et al 2022 ; Xu et al 2020 ). In this study, we observed an increase in the expression level of Lc MFN2 following poly(I:C) stimulation, suggesting its potential involvement in the regulation of antiviral immune responses.…”
Section: Discussionmentioning
confidence: 99%